Stocking density optimisation of pangasius (Pangasianodon hypophthalmus) fingerlings with basil (Ocimum basilicum L.) in nutrient film technique (NFT) based aquaponics: Stocking density optimisation in nutrient film technique (NFT) based aquaponics - Neerudu Harika; Verma, Ajit Kumar; Krishnani, Kishore Kumar; Hittinahalli, Chandrakant Mallikarjun; Varghese, Tincy; Bharti, Vidya Shree; Singh , Angom Lenin; Farooq, Aatira (Indian Journal of Fisheries, 2023)
An experiment for 90 days was performed to optimise the stocking density of pangasius (Pangasianodon hypophthalmus) with basil (Ocimum basilicum L.) in a nutrient film technique (NFT) based aquaponics. The experiment had four treatments with different stocking densities of pangasius as T1 (2.5 kg m-3), T2 (2.75 kg m-3), T3 (3.0 kg m-3) and T4 (3.25 kg m-3) with a constant plant density of 24 plants m-2 and control viz., C (2.5 kg m-3 without plants). Significant (p<0.05) difference in final body weight of fish was found among the treatments and control. The highest fish biomass was recorded in T3 (10.29±4.41 kg m-3) followed by T4, T2, T1 and C. The highest plant yield was found in T4 (510.90±6.25 g); however, no significant difference was found between T4 and T3. No significant (p>0.05) difference in macro and micronutrient content of basil leaves was recorded in T4 and T3. The physiological parameters (hematological, serum biochemical and anti-oxidant stress enzymes) were found to be within the acceptable range. Considering the water quality parameters, fish growth, total biomass of fish, fish physiological responses, basil yield and nutrient content, the stocking density of 3.00 kg m-3 (pangasius) with 24 plants m-2 of basil could be recommended for basil-pangasius aquaponics. Keywords: Aquaponics, Aquaculture wastewater, Basil, Nutrient film technique, Pangasius